SM 01-2334 Darpi: accelerating injury prevention through the intersection of new concepts in science, practice, and data. (November 2018) - Qualters, Judith
Abstract : For more than 25 years, the United States (US) Centers for Disease Control and Prevention's (CDC) National Center for Injury Prevention and Control (NCIPC) has applied a public health approach to prevent and control violence and injuries. The NCIPC's Division of Analysis, Research and Practice (DARPI's) connects data, research, and practice and is focused on advancing the application of translational research, and specifically implementation science, to population health over the coming years. Collaborations across funded Injury Control Research Centers, State Core Violence and Injury Prevention Programs, and other partners will be highlighted to demonstrate the impact of building connectivity to inform and advance research that is needed for public health practice; approaches to data and evidence translation and dissemination; evaluation in real-world implementation; and building 'on-the-ground' capacity needed for effective evidence integration into public health and community systems. These efforts and the state of the science, have informed DARPI's five-year strategic roadmap aimed at increasing the translation and implementation of effective, scalable violence and injury prevention strategies; establishing core capacities for multi-jurisdictional injury and violence prevention nation-wide; and enhancing the availability, delivery, and usability of violence and injury-related data and information, all with the goal of producing equitable and sustainable reductions in injury and violence across communities.